Biology and ecology of the Oriental flower-breeding Drosophila elegans and related species. Issue 1 (31st December 2022) - Ishikawa, Yuki; Kimura, Masahito T.; Toda, Masanori J.
ABSTRACT: Animals adapt to their environments in the course of evolution. One effective approach to elucidate mechanisms of adaptive evolution is to compare closely related species with model organisms in which knowledge of the molecular and physiological bases of various traits has been accumulated. Drosophila elegans and its close relatives, belonging to the same species group as the model organism D. melanogaster, exhibit various unique characteristics such as flower-breeding habit, courtship display, territoriality, sexual dimorphism, and colour polymorphism. Their ease of culturing and availability of genomic information makes them a useful model for understanding mechanisms of adaptive evolution. Here, we review the morphology, distribution, and phylogenetic relationships of D. elegans and related species, as well as their characteristic flower-dependent biology, food habits, and life-history traits. We also describe their unique mating and territorial behaviours and note their distinctive karyotype and the genetic mechanisms of morphological diversity that have recently been revealed.